Changes in social participation between 1 and 2 years following moderate-severe traumatic brain injury - Hart, Tessa; Rabinowitz, Amanda (Frontiers in Rehabilitation Sciences, 2022)
Objective: To examine patterns of change in social participation in persons with moderate-severe traumatic brain injury (msTBI) between 1 and 2 years postinjury, and predictors of observed change. Participants: 375 participants with msTBI enrolled in a single TBI Model System site. Measures and Methods: The dependent variable in a linear regression was a reliable change score for the Social Relations subscale of the Participation Assessment with Recombined Tools-Objective, administered at 1- and 2-year follow-ups. Predictors of change included demographics, injury severity, social and functional status at Year 1, and changes in function and life circumstances between years 1 and 2. Results: Social participation status did not change substantially for ¾ of the sample, while approximately equal proportions of the remainder improved or declined. The regression model was significant (p<.001). Improvement was predicted by private vs. public insurance and decline was predicted by a reduction in the FIM functional outcome measure from year 1 to year 2. Marginal predictors included education (higher levels predicting improvement) and year 1 marital status (single status predicting decline). Conclusions: Longitudinal change in social participation in the chronic phase of msTBI deserves further study, with attention to resource limitations and the impact of changes in functional status.